Does Students’ Habit in Watching English Movies and Ability in Translating English Idioms Correlate? - Sukatri, Ifal; Ardi, Havid (Universitas Negeri Padang, 2024)
Most previous researchers found out that students have difficulties in transalting some expressions from a source language to a target language. This research has a purpose to reveal correlation between the students’ habit in watching English movies and their ability in translating English idiom expressions. The population and sample of this research was the third year who are taking translation subject in their fifth semester of academic year 2021 in English Department of Universitas Negeri Padang. The instruments of this research were questionnaire and translation test. The result of this research showed that the r-calculated (0.549) > r-table (0.333). The hypothesis was accepted by the calculation of t-test which is t-calculated (3.773) > t-table (1.692) with df = n-2 (33) in the level of significance 0.05. The research hypothesis stated that there is a significant correlation between students’ watching habits and their ability in translating English idioms was accepted.